Gamification : influencing value-perception of target behaviors - Hsueh, Vivian Hua Chen (2018)
Existing scholarship of gamification has covered the effectiveness of different types of game design elements in specific applications. There is a need to understand why gamification may be capable of fulfilling these applications’ goals and how effective gamified experiences can be created or facilitated. This paper aims to fill a gap in gamification theory by focusing on the goal driving the implementation of gamification and highlighting the ways by which it affects the perception based psychological processes that influence user behavior. Gamification is conceptualized here as the use of game elements to influence users’ value perceptions of a target behavior in order to motivate action. This study suggests new approaches to gamification implementations and hopefully opens new avenues for further theoretical development following this conceptualization are suggested.